Q: 6+7(x-5)=4-3(x-5)

A: 6+7(x-5)=4-3(x-5) 6 + 7x -35 = 4 - 3x +15 7x +3x = 4 +15 + 35 -6 10x = 48 x = 48/10 = 4.8

Expert answered|coolcatrina|Points 403|

Question

Asked 6/18/2012 11:51:34 PM

Updated 12/24/2014 5:23:39 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by SCM [12/24/2014 5:23:39 AM]

Rating

0

6+7(x-5)=4-3(x-5)

6 + 7x -35 = 4 - 3x +15

7x +3x = 4 +15 + 35 -6

10x = 48

x = 48/10 = 4.8

6 + 7x -35 = 4 - 3x +15

7x +3x = 4 +15 + 35 -6

10x = 48

x = 48/10 = 4.8

Added 12/24/2014 5:23:37 AM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [12/24/2014 11:58:39 AM]

27,000,829 questions answered

There are no comments.